2013
DOI: 10.1128/iai.00263-13
|View full text |Cite
|
Sign up to set email alerts
|

Protective Humoral Immunity Elicited by a Needle-Free Malaria Vaccine Comprised of a Chimeric Plasmodium falciparum Circumsporozoite Protein and a Toll-Like Receptor 5 Agonist, Flagellin

Abstract: bImmunization with Plasmodium sporozoites can elicit high levels of sterile immunity, and neutralizing antibodies from protected hosts are known to target the repeat region of the circumsporozoite (CS) protein on the parasite surface. CS-based subunit vaccines have been hampered by suboptimal immunogenicity and the requirement for strong adjuvants to elicit effective humoral immunity. Pathogen-associated molecular patterns (PAMPs) that signal through Toll-like receptors (TLRs) can function as potent adjuvants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 68 publications
2
15
0
Order By: Relevance
“…Previous studies have reported that inbreed mice immunized with T1BT* constructs have in their serum IgG subtypes associated with both Th1 and Th2 cellular responses [59], [91]. We found that DR4 transgenic mice immunized with T1BT*-Y initially have respectively stronger Th2–associated IgG1 and Th1-associated IgG2/b response than T1BT* immunized mice.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have reported that inbreed mice immunized with T1BT* constructs have in their serum IgG subtypes associated with both Th1 and Th2 cellular responses [59], [91]. We found that DR4 transgenic mice immunized with T1BT*-Y initially have respectively stronger Th2–associated IgG1 and Th1-associated IgG2/b response than T1BT* immunized mice.…”
Section: Discussionsupporting
confidence: 52%
“…The TLR5 agonist flagellin has been proven as an effective mucosal adjuvant, in addition to its systemic adjuvant activity [5], when administered via the i.n. route [6,7], which can prominently increase a protective IgA response [8,9]. However, the mechanism by which flagellin drives a mucosal immune response when acting as an i.n.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it remains unclear what amino acid regions from the hypervariable domains mitigate this third unknown pathway and whether this attribute is shared by other flagellin molecules or limited to close relatives of FliC. Nempont and colleagues (30) described three different FliC deletions D204-292, D191-352, and D174-400 that had reduced immunogenicity, although the most severely attenuated mutants were the D191-352 and D174-400 deletions, suggesting that the D2 domain may be the most critical for MyD88-independent IgG1 anti-flagellin responses (33,41). Future studies using flagellin from L. monocytogenes and S. adelaide to define the precise structures on D2/D3 that are required to enhance Ab production will be helpful to understand FliC's biological activity and also for vaccine development.…”
Section: Immunohorizonsmentioning
confidence: 99%
“…The D2 and the D3 domains (D2/D3) of FliC are largely exposed on the outer surface of the flagellar filament, and are the regions of the protein that are recognized by serotype specific Abs during natural Salmonella infections (28,29). Although most studies have implicated the TLR5 recognition site of FliC as the critical component of flagellin's adjuvancy and immunogenicity, there are additional reports that suggest the D2/D3 domain of flagellin is a contributing factor (30)(31)(32)(33). Thus, there is precedence for anti-flagellin Ab responses being influenced by structures other than the well-characterized TLR5 (D1) and Naip5/6 (D0) recognition sites.…”
Section: Introductionmentioning
confidence: 99%